Analisis Dugaan Pencemaran Nama Baik Azizah Salsa: Kajian Linguistik Forensik - Syanata, Amanda Putri; Muliana, Dina; Andini, Fitri; Melinda, Gita; Tanjung, Nissa Azahra; Aprilia, Ririn; Siregar, Mustika Wati (Journal of Citizen Research and Development, 2025)
This study aims to analyze the language used in the case of alleged defamation on social media (TikTok) using forensic linguistic theory. This research focuses on analyzing the content of linguistic data to identify elements of defamation. The approach in this study uses descriptive qualitative. The research focuses on language analysis in TikTok videos on October 21, 2024, which allegedly contain elements of defamation. The results of this study were analyzed using two steps, namely through semantic analysis and pragmatic analysis. defamation analysis using semantic and pragmatic analysis found that Jessika shared her post with the audience, giving remarks in the form of accusations against Azizah (Zize) If she cheated on Salim and had evidence of her infidelity.